Psychological Resources of Adolescents' Achievement: Differential Aspects - A.M. Potanina; V.I. Morosanova (Психолого-педагогические исследования)
In recent years, psychologists pay more and more attention to the study of individual typological characteristics of people. The introduction adduces the purpose of the article - to analyze current trends in the study of non-cognitive predictors of adolescent achievement and summarize new data obtained in empirical studies of psychological resources of academic success. The first section of the article analyzes in detail the recent foreign studies of the most significant (according to meta-analyses) psychological resources of academic performance within the framework of an individual-oriented approach. Among the new trends, there is a focus on studying the profiles of psychological resources of academic achievement and their stability in different age periods, as well as an interest in predicting academic performance depending on the type of profile. The second section of the article analyzes the results of empirical studies of the students’ individual characteristics in the context of the differential-typological approach, conducted at the Psychological Institute of the Russian Academy of Education. The authors considered typologies created in the framework of studying the temperamental and characterological foundations of students' conscious self-regulation. They describe empirical typologies of special regulatory resources for achieving educational goals, including examination success. The research results allowed to develop the generalized ideas about age-related differential-typological differences in the regulatory and personal resources of academic achievement of the basic and high school students. The conclusion is made about the resource role of conscious self-regulation and school engagement in maintaining students’ academic performance. The studies demonstrated the predictive effect of conscious self-regulation on academic performance and school engagement during the students’ transition to high school. The conclusive part emphasized the practical significance of supplementing the studies of general patterns of manifestation of the psychological resources of academic performance with an analysis of students’ individual-typological characteristics which can be fruitful for the development of an individual approach in education.